Superior mediastinal typical carcinoid detected by 99mTc-MIBI SPECT/CT imaging: A case report. Issue 52 (December 2017) - Lu, Chenghui; Wang, Zenghua; Wang, Guoqiang; Wang, Xufu; Liu, Xinfeng
Abstract: Rationale: This is a rare case of mediastinal typical carcinoid tumor with elevated parathyroid hormone (PTH) and hypercalcemia detected by 99m Tc -methoxy-isobutyl-isonitrile( 99m Tc-MIBI) single photon emission computed tomography/computed tomography (SPECT/CT) imaging. Patient concerns: A 65-year-old male patient presented with hypercalcemia and elevated PTH. Diagnoses: The preoperative diagnosis was ectopic parathyroid adenoma in the right superior mediastinum. Interventions: We performed endoscopic removal of the mass in the superior mediastinum. Outcomes: Histopathology and immunohistochemistry revealed typical carcinoid. Lessons: The differential diagnosis of mediastinal tumors with elevated PTH detected by 99m Tc-MIBI dual-phase imaging should include ectopic parathyroid adenoma as well as carcinoid.